Effect of inter-particle interactions on the magnetic properties of magnetite nanoparticles after coating with dextran - Sreeja, V.; Joy, Pattayil Alias (International Journal of Nanotechnology, 2011)
Nanoparticles of magnetite (Fe3O4) are synthesised by a coprecipitation method and coated with the biocompatible polymer, dextran. The uncoated and dextran coated magnetite nanoparticles are characterised by powder X-ray diffraction, infrared spectroscopy, transmission electron microscopy, and magnetic measurements. The magnetic properties of the uncoated and coated magnetite nanoparticles are compared to study the effect of inter-particle magnetic interactions on the magnetic characteristics. Absence of magnetic hysteresis at room temperature indicates the superparamagnetic nature of the two samples. Evidence for the effect of reduced inter-particle magnetic interactions is directly obtained from the field dependence of magnetisation at room temperature. The decreased superparamagnetic blocking temperature and the nature and shape of the field cooled magnetisation curve of the dextran coated sample further confirmed that the inter-particle magnetic interactions are completely suppressed after coating.
Keywords: dextran coating; magnetic interactions; magnetic properties; magnetite; Nanoparticles